2022
DOI: 10.1097/pq9.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Initiative to Improve After-visit Summary Distribution in Orthopedic Outpatient Clinics

Abstract: Introduction: Communication and patient education are key to effective healthcare encounters and improved health outcomes. The after-visit summary (AVS) is an integral communication and education tool for patients and families. Without effective communication, gaps in comprehension may result in decreased satisfaction with medical encounters, lack of adherence to recommended treatment plans, missed appointments, and increased malpractice claims. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…As noted by Williamson et al, healthcare workers are more invested in interventions when provided with real-time feedback and a way to appreciate their progress visually. 16 Periods of decreased completion rates corresponded with times when feedback was not being provided to clinicians, highlighting the pivotal role of education and reinforcement in sustaining these goals. Functionally, the EMR did not consolidate the AVS of several providers for one patient into one composite document.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Williamson et al, healthcare workers are more invested in interventions when provided with real-time feedback and a way to appreciate their progress visually. 16 Periods of decreased completion rates corresponded with times when feedback was not being provided to clinicians, highlighting the pivotal role of education and reinforcement in sustaining these goals. Functionally, the EMR did not consolidate the AVS of several providers for one patient into one composite document.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, limited literature addresses maximizing its effectiveness in pediatric populations or the unique context of multidisciplinary clinics. [14][15][16] Although the AVS has the potential to facilitate shared decision-making and effective communication, some studies have shown its design is not consistently optimized to convey valuable information clearly and understandably. 17 One primary challenge in patients' adoption and use of AVS patient instructions is the presence of medical jargon within providers' documentation.…”
Section: Introductionmentioning
confidence: 99%